DIMINISHED IMPUTABILITY: A CONTRADICTION IN COSTA RICAN CRIMINAL LAW? - Ruiz Murillo, Adriana (2024)
In a democratic and legal State like ours, the imposition of a sentence requires a judicial process with all the constitutional guarantees, especially for the subject accused of committing a crime. Using the instrument of the Theory of Crime, it is analyzed if the conduct has been described as a crime in criminal regulations, and if it violates the legal system. But the most relevant for the purposes of this article is the analysis of guilt, since it must be determined if the person had the capacity to understand the illegality of the action he was carrying out and if he could behave according to that knowledge, that is, if the person may be imputable. But there are particular conditions that may be presented by those who carry out an illegal action, which exempt them from that responsibility by not being fully aware of the breach of the law that they are carrying out, whether due to mental illness, or serious disturbance of conscience. Those who carry out the action under this condition are called non-imputable, and according to our criminal law, they do not deserve to receive a penalty, but rather a security measure that allows them to receive the medical treatment they need, and provide them with a safe place to the extent of their dangerousness. There is a third possible state that the doctrine has called diminished imputability or semi-imputability, and in this category are those who act with a reduced capacity, for the same reasons as the unimputable person, but without completely losing their consciousness or will. It is in these cases where our legal system is contradictory, since it establishes the obligation to impose a security measure, but recognizes a situation of diminished accountability where it only mitigates the penalty, as is the case of acting under a state of violent emotion. The question arises: should our Penal Code be reformed so that anyone who acts under reduced imputability receives a penalty proportional to the level of reproach that their specific case supports, and if applicable, additionally receives the medical or therapeutic treatment that they require? Or should the security measure be maintained for all these cases as established in the current standard?